Click coupling of flavylium dyes with plasmodione analogues: towards new redox-sensitive pro-fluorophores - Dupouy, Baptiste; Cotos, Leandro; Binder, Annika M.; Slavikova, Lucie; Rottmann, Matthias; Mäser, Pascal; Jacquemin, Denis; Ganter, Markus; Davioud-Charvet, Elisabeth; Elhabiri, Mourad (Chemistry - a European journal, 2025)
The development of redox-sensitive molecular fluorescent probes for the detection of redox changes in Plasmodium falciparum-parasitized red blood cells remains of interest due to the limitations of current genetically encoded biosensors. This study describes the design, screening and synthesis of new pro-fluorophores based on flavylium azido dyes coupled by CuAAC click chemistry to alkynyl analogues of plasmodione oxide, the key metabolite of the potent redox-active antimalarial plasmodione. The photophysical and electrochemical properties of these probes were evaluated, focusing on their fluorogenic responses. The influence of both the redox status of the quinone and the length of the PEG chain separating the fluorophore from the electrophore on the photophysical properties was investigated. The fluorescence quenching by photoinduced electron transfer is reversible and of high amplitude for probes in oxidized quinone forms and fluorescence is reinstated for reduced hydroquinone forms. Our results demonstrate that shortening the PEG chain has the effect of enhancing the fluorogenic response, likely due to non-covalent interactions between the two chromophores. All these systems were evaluated for their antiparasitic activities and fluorescence imaging suggests the efficacy of the fluorescent flavylium dyes in P. falciparum-parasitized red blood cells, paving the way for future parasite imaging studies to monitor cellular redox processes.